A physics-based fast algorithm for structural responses of generalized rotationally axisymmetric structures: the generalized rotation-superposition method - Yang, Mao; Zhang, Jun; Chen, Hao; Yang, Jialin; Mao, Yongjian (Latin American Journal of Solids and Structures, 2024)
Fast calculations are widely required in the traditional applications and the emerging digital twin fields. For those considerations, a novel physics-based fast algorithm, namely generalized rotation-superposition method, is proposed for fast calculating linear elastic responses of generalized rotationally axisymmetric structures under arbitrary mechanical loads. This improved method breaks through the limitations of the previous basic rotation-superposition method in rotational similarity of load and structural axisymmetry, and greatly expands its application scope. In this paper, firstly, the basic theory of the rotation-superposition algorithm is introduced; secondly, the theoretical model of the generalized rotation-superposition method is established; thirdly, the effectiveness and accuracy are verified by using finite element simulations; finally, through a complex case study, the applicability of the generalized rotation-superposition method for complex engineering problems and its advantages in efficiently obtaining massive amounts of data are further illustrated.